SWEDEN’S NEW PUBLIC HEALTH POLICY NATIONAL PUBLIC HEALTH OBJECTIVES FOR SWEDEN - Ågren, Gunnar (2006)
As a result of the Swedish Parliament, the Riksdag, passing the Government’s Public Health Objectives Bill in April 2003, Sweden now has a national public health policy.